2015
DOI: 10.1097/brs.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Functional Limitations Due to Lumbar Stiffness in Adults With and Without Spinal Deformity

Abstract: LSDI scores are low among asymptomatic volunteers, although stiffness-related disability increases with increasing age. Patients with ASD report substantial stiffness-related disability even prior to surgical fusion. Stiffness-related disability correlates with pain- and function-related disability measures among patients with spinal deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Elderly patients spend a lot of time indoors and do not generally participate in a great deal of outdoor activity like younger patients. Most of the questions in LSDI are about indoor activity and, thus, we believe LSDI may be a valid instrument for daily function assessment in ADS patients after fusion surgery. In our study, LSDI in + grade PI‐LL and ++ grade PI‐LL was significantly higher than that in 0 grade PI‐LL, but no statistical difference was observed between them.…”
Section: Discussionmentioning
confidence: 46%
“…Elderly patients spend a lot of time indoors and do not generally participate in a great deal of outdoor activity like younger patients. Most of the questions in LSDI are about indoor activity and, thus, we believe LSDI may be a valid instrument for daily function assessment in ADS patients after fusion surgery. In our study, LSDI in + grade PI‐LL and ++ grade PI‐LL was significantly higher than that in 0 grade PI‐LL, but no statistical difference was observed between them.…”
Section: Discussionmentioning
confidence: 46%
“…When interpreting the findings of this review it is important to note that degenerative change and normal ageing contribute to decreased flexibility and increased stiffness in the adult spine [34]. Spinal stiffness in particular is increased in patients with spinal deformity [35]. Thus, it is plausible that the spine of an adult with scoliosis may be significantly more resistant to the influence of external corrective forces such as those being exerted by a spinal brace/orthosis.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between scoliosis and pain might be mediated by variables other than the curve itself. It has been shown that compared with asymptomatic volunteers, baseline data on lumbar stiffness evaluated by means of Lumbar Stiffness Disability Index (LSDI) correlates with pain (Pearson correlation “r” LSDI versus SRS-22 Pain: −0–749) and functional limitations (LSDI vs SRS-22 Function: −0.760) in patients with spinal deformity [ 67 ].…”
Section: Adolescent Idiopathic Scoliosis (Ais) and Back Painmentioning
confidence: 99%